THE EFFECT OF THE ONE-TIER, TWO-TIER, AND THREE-TIER DIAGNOSTIC TEST TOWARD THE STUDENTS' CONFIDENCE AND UNDERSTANDING TOWARD THE CONCEPTS OF ATOMIC NUCLEAR - Yusrizal, Yusrizal; Halim, A (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
The identification of misconception in the Physics or Science learning all this time mostly used the two-tier or three-tier diagnostic test. There were several reasons why both test forms used, such as to make sure whether the students guessed the answers or understood the concepts. Besides, through the use of both tests the students' confidence in choosing the answers could be identified. However, there was no explanation or study on the most effective test to identify those misconceptions. The purpose of this study was to know the effect of the one-tier, two-tier and three-tier diagnostics test toward the students' answer pattern, confidence level, and understanding on the concept of anatomic nuclear. The respondents which were used in this survey research were 88 the students attending Atomic Nuclear course in Physics Education Department, Faculty of Teacher Training and Education, Syiah Kuala University. Some tests were consecutively given to the 88 respondents, the test participants could continue to the next test if they finished all questions in the previous test. The data collection used the instrument of basic Physics preconception test (Tes Pemahaman Konsep Fisika Inti/TPKFI) in the form of one-tier, two-tier and three-tier multiple choice with eight multiple choice items. The test was developed by researchers with difficulty index = 0.35, discrimination index = 0.31, validity= 0.35, and reliability= 0.90. The data analysis result showed that even though the students' answer patterns were the same for all types of diagnostic tests, there was a convincing change in the students' concept understanding and confidence between the two-tier and three-tier. From this research, it could be inferred that the identification of the students' misconception in the Science learning would be better (had high confidence), if the diagnostic test used was higher, that was three-tier, four-tier, and thus on.